Genetically based latitudinal clines in Artemisia californica drive parallel clines in arthropod communities. Issue 1 (9th December 2016) - Pratt, Jessica D.; Datu, Andrew; Tran, Thi; Sheng, Daniel C.; Mooney, Kailen A.
Abstract: Intraspecific variation in plant traits has been clearly shown to drive the structure of associated arthropod communities at the spatial scale of individual plant populations. Nevertheless, it is largely unknown whether plant trait variation among populations drives landscape‐scale variation in arthropod communities, and how the strength of such plant genetic effects compares to, and interacts with, those of environmental variation. We documented the structure of arthropod communities on Artemisia californica for two consecutive years in a common garden of plants sourced from five populations along a 5° latitudinal gradient and grown under precipitation treatments approximating the four‐fold difference between the north and south range margins for this species. Previous study of plant traits from this garden documented clinal genetic variation, suggesting local adaptation to this environmental gradient, as well as effects of precipitation manipulation that were consistent among populations (i.e., no genotype‐by‐environment interaction). Within the common garden, arthropod density, evenness, and diversity increased clinally with population source latitude, and arthropod community composition (i.e., species relative abundance) showed a north‐south divide. The 2.6‐fold cline of northward increase in arthropod density in the common garden was mirrored by a 6.4‐fold increase in arthropod density on wild plants sampled along the species range. In contrast to the strong influence of plant genotype, the precipitation manipulation only influenced arthropod community composition, and plant genetic effects on arthropods operated independently of precipitation regime (no genotype‐by‐environment interaction). Accordingly, we conclude that the strongest driver of landscape‐level variation in arthropod communities in this foundational plant species is not variation in the abiotic environment itself, but rather variation in plant traits underlain by the evolutionary process of plant local adaptation.